Erucin, the Major Isothiocyanate in Arugula (Eruca sativa), Inhibits Proliferation of MCF7 Tumor Cells by Suppressing Microtubule Dynamics - Azarenko, Olga; Jordan, Mary Ann; Wilson, Leslie (PloS one, 2014)
Consumption of cruciferous vegetables is associated with reduced risk of various types of cancer. Isothiocyanates including sulforaphane and erucin are believed to be responsible for this activity. Erucin [1-isothiocyanato-4-(methylthio)butane], which is metabolically and structurally related to sulforaphane, is present in large quantities in arugula (Eruca sativa, Mill.), kohlrabi and Chinese cabbage. However, its cancer preventive mechanisms remain poorly understood. We found that erucin inhibits proliferation of MCF7 breast cancer cells (IC50 = 28 µM) in parallel with cell cycle arrest at mitosis (IC50 = 13 µM) and apoptosis, by a mechanism consistent with impairment of microtubule dynamics. Concentrations of 5-15 µM erucin suppressed the dynamic instability of microtubules during interphase in the cells. Most dynamic instability parameters were inhibited, including the rates and extents of growing and shortening, the switching frequencies between growing and shortening, and the overall dynamicity. Much higher erucin concentrations were required to reduce the microtubule polymer mass. In addition, erucin suppressed dynamic instability of microtubules reassembled from purified tubulin in similar fashion. The effects of erucin on microtubule dynamics, like those of sulforaphane, are similar qualitatively to those of much more powerful clinically-used microtubule-targeting anticancer drugs, including taxanes and the vinca alkaloids. The results suggest that suppression of microtubule dynamics by erucin and the resulting impairment of critically important microtubule-dependent cell functions such as mitosis, cell migration and microtubule-based transport may be important in its cancer preventive activities.